2015
DOI: 10.1177/0363546515590221
|View full text |Cite
|
Sign up to set email alerts
|

Femoral and Tibial Graft Tunnel Parameters After Transtibial, Anteromedial Portal, and Outside-In Single-Bundle Anterior Cruciate Ligament Reconstruction

Abstract: The AMP and OI surgical techniques were superior in positioning the ACL femoral tunnel at the center of the native ACL attachment site compared with the TT technique. An acceptable graft fixation length was obtained for all 3 surgical techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 42 publications
5
53
0
2
Order By: Relevance
“…These different results may be caused by a less-standard starting point of the tibial tunnel, which remained compromised with nonanatomic ACL reconstruction. In contrast, of the 19 studies with anatomic ACL reconstruction, only two [24,28] demonstrated that the angle of the femoral tunnel in the coronal plane was less than 30˚, thus showing a much more oblique tunnel than in the studies quoted previously that used anatomic ACL reconstruction. Therefore, a considerably oblique femoral tunnel angle, which may result in more repetitive bending stress on the graft at the femoral tunnel opening, should be avoided because of increased abrasive force at the contact area on the sharp edge of the bone tunnel opening.…”
Section: Plos Onementioning
confidence: 63%
“…These different results may be caused by a less-standard starting point of the tibial tunnel, which remained compromised with nonanatomic ACL reconstruction. In contrast, of the 19 studies with anatomic ACL reconstruction, only two [24,28] demonstrated that the angle of the femoral tunnel in the coronal plane was less than 30˚, thus showing a much more oblique tunnel than in the studies quoted previously that used anatomic ACL reconstruction. Therefore, a considerably oblique femoral tunnel angle, which may result in more repetitive bending stress on the graft at the femoral tunnel opening, should be avoided because of increased abrasive force at the contact area on the sharp edge of the bone tunnel opening.…”
Section: Plos Onementioning
confidence: 63%
“…Another possible explanation for our results is that, during femoral tunnel placement with the conventional transtibial technique, the guide pin and drill often need to be torqued and drilling is not concentric; in the outside-in technique, femoral tunnel placement is not forced by the tibial tunnel, as shown by Chambra et al [23]. Moreover, in a recent cadaveric study, Osti et al [24] showed that the outside-in portal surgical technique was superior at positioning the ACL femoral tunnel at the center of the native attachment site when compared with the standard transtibial technique. In fact, drilling the femoral tunnel separately from and unrelated to the tibial tunnel could achieve a more anatomical femoral insertion.…”
Section: Discussionmentioning
confidence: 68%
“…Transportal, transtibial, and outside-in techniques are the most popularly used methods. 28,74,79,87,97 The transportal technique can easily reach the center of the native ACL footprint. However, deep-knee bending is required when creating the femoral tunnel using this method, and insufficient femoral tunnel length and iatrogenic femoral chondral tear are potential complications.…”
Section: Discussionmentioning
confidence: 99%